God and phenomenal consciousness : a novel approach to knowledge arguments - Nagasawa, Yujin (Cambridge University Press, 2008)
"In God and Phenomenal Consciousness, Yujin Nagasawa bridges debates in two distinct areas of philosophy: the philosophy of mind and the philosophy of religion. First, he introduces some of the most powerful arguments against the existence of God and provides new objections to them. He then presents a hitherto unrecognised parallel structure between these arguments and influential arguments offered by Thomas Nagel and Frank Jackson against the physicalist approach to phenomenal consciousness. By appealing to this structure, Nagasawa constructs novel objections to Jackson's and Nagel's arguments. Finally, he derives, from the failure of these arguments, a unique metaphysical thesis, which he calls 'non-theoretical physicalism'. Through this thesis, he shows that although this world is entirely physical, there are physical facts that cannot be captured even by complete theories of the physical sciences"--Publisher description